Motivation of Mothers Who Have Toddlers to Come to The Posyandu to Monitor Children's Growth and Development Using The Motivation for Health Behavior Scale (MHBS) - Rochmawati, Rochmawati (Jurnal Kebidanan Sorong, 2025)
This study aims to measure mothers' motivation in bringing toddlers to Posyandu using the Motivation for Health Behavior Scale (MHBS), analyze the relationship between sociodemographic factors and mothers' motivation, and assess the relationship between motivation levels and Posyandu visit frequency. Using a cross-sectional design, the study involved 76 mothers with toddlers in Ciseeng District, Bogor Regency. Results showed that autonomous motivation had the highest mean (3.86±0.74), with education and family support significantly correlating with autonomous motivation (r=0.412; p=0.007 and r=0.388; p=0.008). Autonomous motivation significantly correlated with regular Posyandu visits (χ²=9.647; p=0.002). Interventions should focus on strengthening internal motivation to increase Posyandu participation.